2019
DOI: 10.1016/j.biomaterials.2018.08.057
|View full text |Cite
|
Sign up to set email alerts
|

3-D physiomimetic extracellular matrix hydrogels provide a supportive microenvironment for rodent and human islet culture

Abstract: Organ-on-a-chip platforms serve as cost-efficient testbeds for screening pharmaceutical agents, mimicking natural physiology, and studying disease. In the field of diabetes, the development of an islet-on-a-chip platform would have broad implications in understanding disease pathology and discovering potential therapies. Islet microphysiological systems are limited, however, by their poor cell survival and function in culture. A key factor that has been implicated in this decline is the disruption of islet-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 101 publications
1
70
0
3
Order By: Relevance
“…Only in the recently published study by Sackett et al were the basement membrane proteins retained when the pancreatic tissue was decellularized and processed in a hydrogel form. 22 In other previously published studies, 17,21 a limited retention of collagen IV was reported, while laminin proteins were either not detected or investigated. In our study, only hydrogels treated with 1% Triton showed retention of laminin proteins, despite being lower when compared with native tissue ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Only in the recently published study by Sackett et al were the basement membrane proteins retained when the pancreatic tissue was decellularized and processed in a hydrogel form. 22 In other previously published studies, 17,21 a limited retention of collagen IV was reported, while laminin proteins were either not detected or investigated. In our study, only hydrogels treated with 1% Triton showed retention of laminin proteins, despite being lower when compared with native tissue ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 94%
“…6,7 In particular, basement membrane proteins have been shown to play an important role in maintaining beta-cell functionality, both in vivo 8 and in vitro. [9][10][11][12] Among the different scaffolds evaluated for 3D culture of islets or beta-cell lines, several decellularized tissues have recently been explored, including the pancreas, [13][14][15][16][17][18][19][20][21][22] liver, 23 lung, 21 or small intestine submucosa. 24,25 Tissue-derived biomaterials can closely mimic the microenvironment of the endogenous tissue, making them potentially more advantageous for tissue repair or in vitro models compared with other biologic or synthetic scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiated hESCs offer a potentially unlimited number of cells for this purpose [19], and this approach is enhanced by improving the maturation of the generated SC-β cells [20]. The inclusion of endothelial cells with SC-β cells could be combined with macroporous scaffolds that enable retrievability [16,21] or other beneficial materials [22][23][24][25][26] to develop a more comprehensive transplantation strategy for diabetes. An alternative cell type to SC-β cells are earlier pancreatic progenitors derived from hESCs.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been explored that utilize the pancreas as tissue source including repopulating decellularized pancreas [162][163][164][165], culturing islets on decellularized pancreas [166], and differentiating stem cells into βcells using β-cell line produced matrix [167]. Techniques have also included other tissue sources and methods such as processing decellularized ECM into hydrogels [168,169] and culturing islets on decellularized liver [170]. Pancreatic or liver matrices have been used inside an encapsulation device [171], and construction of a bilayer transplantation device was accomplished from porcine pericardium and tendon [172].…”
Section: Matrix Mimicry and Vascularization-survival And Engraftment mentioning
confidence: 99%